Stenting of renal artery with or without predilatation in hypertensive patients with renal artery stenosis: Results of the nine-months follow-up - Ilkay, Erdo?an; Yavuzkir, Mustafa; Da?li, Necati; Akbulut, Mehmet; Karaca, Ilgin; Arslan, Nadi (My University, 2003)
Objective: We evaluated the effects of stenting on blood pressure and renal functions in hypertensive patients with proximal/ostial atherosclerotic renal artery stenosis. Methods: Twenty-six hypertensive patients (9 female, 17 male, mean age 59.0±7.4 years) who had renal artery stenosis were included into this study. Their blood pressure, urea and creatinine levels were measured at 24 hours, 3 months and 9 months after procedure. Results: Stents were implanted successfully in all cases. Implanting of stent was done with predilatation in 16 (5 %) cases and without predilation (direct stenting) in 10 (49%) cases. Mean stent diameter and stent length were 7.11±0.3 mm and 15.0±2.2mm respectively. The antihypertensive drug therapy was stopped in 6 (23%) patients, decreased in 15 patients (58 %) and did not change in 5 (19 %) patients. No significant changes were observed in urea and creatinine levels. However, creatinine levels were lower after procedure in direct stenting patients than in patients in whom predilation was applied (0.78±0.3 mm; 1.32±0.6, p=0.003). This difference disappeared on the 3rd month of follow-up. One patient died during follow-up period. Control angiography was performed in 23 patients. Angiographic restenosis was found in 1 (4.3%) patient. Major events during follow-up period occured in 2 (8 %) patients. Conclusion: Stenting in hypertensive patients with renal artery stenosis is reliable and effective procedure. Selection the stenting procedure with or without predilatation depends on the clinical status of patients and the choice of the interventional team.
Renal arter darli?i saptanan hipertansif hastalarda renal artere stent uygulamasi: Dokuz aylik takip sonuçlari
Keywords: Antihypertensive Agents; Arteriosclerosis; Blood Pressure; Dilatation; Female; Humans; Hypertension, Renal; Kidney Function Tests; Male; Middle Aged; Renal Artery Obstruction; Severity of Illness Index; Stents; Treatment Outcome; acetylsalicylic acid; antihypertensive agent; clopidogrel; creatinine; heparin; ticlopidine; urea; adult; aged; antihypertensive therapy; artery dilatation; artery prosthesis; article; blood pressure measurement; clinical article; clinical trial; controlled clinical trial; controlled study; creatinine blood level; death; drug dose reduction; female; follow up; human; human tissue; hypertension; intermethod comparison; kidney angiography; kidney artery stenosis; kidney function; male; nephrosclerosis; postoperative period; reliability; restenosis; stent; surgical technique; treatment indication; treatment outcome; urea blood level